Redesign of Production Floor Layout Using Systematic Layout Planning (SLP) Method - Mahesa Yudha Erdiansyah; Joumil Aidil SZS (Yayasan Riset dan Pengembangan Intelektual, 2024)
PT XYZ is a manufacturing company engaged in printing and packaging, one of their products is wafer roll packaging. The problem that occurs in this company is the lack of consideration of the degree of nearness at work stations, the placement of work stations that are not in the sequence of the production process that causes backtracking. This research used Systematic Layout Planning (SLP) method and Blocplan Software to determine the layout redesign on production floor. From the research that was conducted, layout 4 was obtained as the best proposed layout with an R score of 0.88 and several changes were made to the position of the work station placement. The proposed layout obtained a total distance between work stations of 426 meters from the total distance between work stations of the initial layout that was 670 meters, which obtained a difference of total distance from work stations between initial layout and proposed layout was 244 meters.